Effectiveness of 5-Fluorouracil 5% Cream in Perianal Condylomata Accuminata Treatment: A Case Report - Dea Florensia; Lita Setyowatie (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Condylomata accuminata is a sexually transmitted disease, appeared as verrucous or cauliflower-like papules or warts in the anogenital. It is caused by human papillomavirus (HPV), mostly type 6 and 11. The ideal therapy should be simple, inexpensive, effective, does not cause side effects, and can be used by the patient himself. Purpose: To assess the effectiveness of 5-Fluorouracil (5-FU) 5% cream therapy for perianal condylomata accuminata treatment. Case: A 24-year-old male presented with a chief complaint of warts around the anal area that multiplied in the past 3 weeks. The acetowhite test was positive. The patient was diagnosed with condylomata accuminata perianal. The patient received 5-FU 5% cream, applied 3 times a week to the lesions for 5 weeks. After 5 weeks, no new warts were found. Discussion: 5-FU 5% cream is a therapeutic option for perianal wart lesions that easily applied, inexpensive, effective, does not cause side effects, and can be used by the patient himself. It is well known as an antimetabolite with a cytotoxic effect that occurs through a mechanism of disruption in the normal synthesis and function of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). The treatment with 5-FU 5% cream 3 times a week for 5 weeks provided good results with no side effects were reported. Conclusion: The application of 5-FU 5% cream was a modality of self-application treatment that effective for perianal condylomata accuminata.